VD_FINDINFO Jug / 2018 / 6 vom 26. Juni 2017 - VD Tribunal cantonal (2017)
DIFFAMATION, FIXATION DE LA PEINE, PEINE PÉCUNIAIRE, TORT MORAL, INDEMNITÉEN GÉNÉRAL, ADMISSION DE LA DEMANDE | 173 ch. 1 CP, 34 CP, 42 al. 1 CP, 47 CP